Literature Review: Hubungan Paparan Asap Rokok dengan Gangguan Saluran Napas Atas (Lembaga Pengembangan Kinerja Dosen, 2026)
Exposure to cigarette smoke is one of the environmental risk factors that is still widely found and has a significant impact on the health of the respiratory system, especially the upper respiratory tract. The irritants and toxic substances in cigarette smoke can trigger mucosal inflammation, interfere with the defenses of the airways, and increase susceptibility to various upper airway disorders. This study aims to systematically analyze the relationship between cigarette smoke exposure and upper airway disorders based on available scientific evidence. The method used is Systematic Literature Review (SLR) with reference to the PRISMA 2020 guidelines. Literature searches were conducted through PubMed, ScienceDirect, Google Scholar, and Garuda databases. Articles were selected based on inclusion and exclusion criteria, resulting in 26 articles that were analyzed narrative-synthesis. The results showed that most studies reported a meaningful association between exposure to cigarette smoke, both in active and passive smokers, and an increased risk of upper respiratory tract disorders such as rhinitis, sinusitis, recurrent upper respiratory tract infections, pharyngitis, and laryngitis. Higher risks are found in passive smokers, especially children, as well as in individuals with long-term, high-intensity exposure. The conclusion of this study confirms that exposure to cigarette smoke is an important and preventable risk factor for upper respiratory tract disorders. Therefore, it is necessary to strengthen the policy of non-smoking areas, public education, as well as promotive and preventive efforts in health services to reduce the impact of exposure to cigarette smoke on the health of the upper respiratory tract.